Competition between co‐occurring invasive and native consumers switches between habitats. (8th October 2018) - Zwerschke, Nadescha; van Rein, Henk; Harrod, Chris; Reddin, Carl; Emmerson, Mark C.; Roberts, Dai; O'Connor, Nessa E.
Abstract: The introduction of a non‐native species frequently has adverse direct effects on native species. The underlying mechanisms, however, often remain unclear, in particular where native and invasive species are taxonomically similar. We found evidence of direct competitive interactions between a globally distributed invasive species (the Pacific oyster, Magallana gigas ) and its native counterpart (the European oyster, Ostrea edulis ). We also discovered that the competitive outcome differed between different habitat types and orientation by identifying context‐dependent responses driven by environmental conditions and stress (i.e. intertidal compared to subtidal habitats; and vertical versus horizontal substratum). This is particularly important because the European oyster is threatened, or in decline, throughout most of its range, and restoration efforts are underway in many regions. We combined experimental manipulations and stable isotope analysis (SIA) to identify the direct effects of competition and the mechanisms by which the invasive and native species compete. We identified negative effects of the invasive species on the native oyster, but these were limited to the subtidal habitat (lower stress environment) and determined by substratum orientation (habitat structure). Crucially, we found that effects of the invasive species on the native species were not always negative and under certain conditions (e.g. on vertical substrata) were positive. Shifts in isotopic niches of both species when co‐occurring, alongside mixing models, indicate that exploitative competition for food is most likely to underpin niche partitioning between both species. We have identified different foraging strategies under different contexts, and our findings highlight the importance of exploitative competition as a driving mechanism behind the co‐occurrence of two seemingly functionally similar consumers. The combination of experimental manipulations with SIA is a powerful tool, and we illustrate how this approach should be incorporated, into multiple environmental contexts at appropriate scales, to more accurately predict impacts of the spread of invasive species on native communities. Abstract : Plain Language Summary